(3eTJgi GdYbhd aj efJgi Gdfbhds - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s
(3ChdgG (B:s
(3HSe Gddg agPG eLehY dWja ef cJGH TQja CYfj cJGH hgh aj CLRGA hajg GdCLRGA gPg CKeGQ ef CTLGQ hCbWGQ ef HMGQ ef ZjQ JHhjH hdG JQJjH efJgi GdCLSGe s
(3BNQgG (B:s
(3hEfj eJYLH ef bhd CUMGH GdYLGFH(B:"(3Ef CYLHgG GdgQejf(B"(3, eY Cf Cbd HQGHj GdUYjO ` HELeGY ef TGgOgG ef Cgd Gdchfjf, CLqd hCced ef YLGFH GdgQejf(B! (3eY Cf HGfj GdgQejf bjd Efg ef CUMGH GdHQGHj, hdcnqf gPG Ydi bOQ eG GWdYhG hUdi Gddg Ydj SjOfG eMeOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3\301s
(3gOjI GdYGQajf (B1\542s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdeYGQa GdYGeIs